2010
DOI: 10.1007/s11136-010-9674-9
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric evaluation of the functional assessment of HIV Infection (FAHI) questionnaire and its usefulness in clinical trials

Abstract: The FAHI demonstrated acceptable psychometric properties in two independent populations. HRQL assessment enabled detection of changes in patients' health status not revealed by traditional efficacy endpoints.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
6

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 43 publications
(44 reference statements)
2
19
6
Order By: Relevance
“…Compared to other studies which utilized FAHI [19, 24, 25], the baseline levels of HRQoL were relatively high in our study. This may have been explained by the fact that baseline assessments were conducted during the acute infection phase and participants had already been receiving care in prevention studies while HIV uninfected.…”
Section: Discussioncontrasting
confidence: 70%
“…Compared to other studies which utilized FAHI [19, 24, 25], the baseline levels of HRQoL were relatively high in our study. This may have been explained by the fact that baseline assessments were conducted during the acute infection phase and participants had already been receiving care in prevention studies while HIV uninfected.…”
Section: Discussioncontrasting
confidence: 70%
“…Although Cronbach’s alpha estimates higher than 0.7 are recommended for group comparison [13, 44], our alpha estimates in the SWB and EWB (0.66, 0.67 respectively) were slightly below the 0.70 estimate, yet remain within the acceptable range. Good alpha estimates were observed in the PWB, FWB and the overall scale.…”
Section: Discussioncontrasting
confidence: 55%
“…The internal consistency of the total scale in these studies was invariably excellent (Cronbach’s α range 0.91–0.92) [17, 22, 3032]. The subscale α coefficients ranged from 0.72–0.92 with the exception of the cognitive function (CF) domain in two studies from South Africa whose α coefficients were slightly below the recommended 0.70 (Cronbach’s α values of 0.65 and 0.60) [13, 17, 22, 3033]. None of these seven studies reported the test-retest reliability of the FAHI.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations